Searching the true poor: Augustine interprets the text of Mt 5:3 - Eguiarte Bendímez, Enrique A. (Mayéutica, 2023)
The article addresses Augustine's explanation of the beatitude Beati pauperes spiritu, quoniam ipsorum est regnum caelorum (Blessed are the poor in spirit, for theirs is the kingdom of heaven), stressing the spiritual implications which Augustine himself highlights in his own exegesis of this text. Namely the identity of the true poor, that include, among other things, humbleness, obedience to God's will, to be related to the Body of Christ and how monk should live poverty. It also addresses the topic of poverty as the first step in a spiritual Journey towards God. Some anti-Donatist ideas regarding poverty are discussed, especially in the relationship of Augustine with the Donatist Bishop Petilian in the Work Contra litteras Petiliani.